2013
DOI: 10.1002/ana.23892
|View full text |Cite
|
Sign up to set email alerts
|

Cell age–specific vulnerability of neurons to anesthetic toxicity

Abstract: Objective Anesthetics have been linked to widespread neuronal cell death in neonatal animals. Epidemiological human studies have associated early childhood anesthesia with long-term neurobehavioral abnormalities, raising substantial concerns that anesthetics may cause similar cell death in young children. However, key aspects of the phenomenon remain unclear, such as why certain neurons die, whereas immediately adjacent neurons are seemingly unaffected, and why the immature brain is exquisitely vulnerable, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 46 publications
(93 reference statements)
4
84
0
1
Order By: Relevance
“…Exposure to isoflurane, however, led to a dramatic increase in the number of caspase-3 immunoreactive cells in the dentate gyrus ( Fig.1), consistent with previous studies. 13,14 Moreover, quantification of caspase-3 immunolabeling in GFP-expressing cells revealed a five-fold increase in double-labeled cells relative to controls. Specifically, in 21-day-old control animals, 2.05±0.75% of GFPexpressing cells co-labeled with caspase-3, while 11.03±1.75% of cells in the P21 anesthesia group expressed caspase-3 ( Fig.1; P<0.001, t-test).…”
Section: Resultsmentioning
confidence: 98%
“…Exposure to isoflurane, however, led to a dramatic increase in the number of caspase-3 immunoreactive cells in the dentate gyrus ( Fig.1), consistent with previous studies. 13,14 Moreover, quantification of caspase-3 immunolabeling in GFP-expressing cells revealed a five-fold increase in double-labeled cells relative to controls. Specifically, in 21-day-old control animals, 2.05±0.75% of GFPexpressing cells co-labeled with caspase-3, while 11.03±1.75% of cells in the P21 anesthesia group expressed caspase-3 ( Fig.1; P<0.001, t-test).…”
Section: Resultsmentioning
confidence: 98%
“…There seems to be a critical period of cellular development during which neurons are susceptible to anaesthesia-induced apoptosis. Vulnerability towards anaesthetics reflects the age of the neurons rather than the age of the organism [15] and is linked to ongoing neurogenesis [28]. In human infants, susceptibility to anaesthetics appears to be restricted to early ages, with very preterm infants exposed before term being at greatest risk [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…In newborn rodents, pigs or non-human primates, an increase of neuronal cell death has been observed following isoflurane exposure [10 -17], with rather subtle long-term cognitive dysfunction occurring in a partially sex-disparate fashion [4,18,19]. Isoflurane-induced neuronal apoptosis appears to occur only at a certain stage of neuronal development, which is dependent on the age of the neuron but independent of the age of the animal [15]. Isoflurane, however, appears to have protective properties as well.…”
Section: Introductionmentioning
confidence: 99%
“…While many of the initial studies established that the window of vulnerability to these agents coincides with the peak developmental period for synaptogenesis, also known as the "brain growth spurt" period, which in rodents occurs primarily at postnatal day 7, but more recent research has shown that anesthetic neurotoxicity risk extends beyond this window (16).…”
Section: S and Early 2000s: Laboratory Animal Experiments Have Sumentioning
confidence: 99%